Role Of Pippali In The Management Of Udarshul - Rawat, Lokendra; Ram, Sunita D; Chouhan, Rinku (International Research Journal of Ayurveda & Yoga, 2020)
In the ancient treatises of Ayurveda different painful condition of abdomen described in udara roga nidan and chikitsa. Mandagni causes improper digestion of ingested food which leads to Udara roga. It is one among the Ashtamahagada. Udarshool seems to be simple but it affects the regular activities. Vata is predominant in Udarshool which can be counteracted by Shoolghna and Vataghna property. Effect of Pippali in the management of shool is beneficial due to its property like vatashaman & dipan etc. Materials And Methods - The literature related to udara roga and pippali available in Charak Samhita, Sushrut Samhia & Astanga Samgraha, Astanga Hridaya, Madhav Nidan, various nighantu etc. with commentaries have been collected in this study. Result- The treatment of udarshool through Ayurvedic approach is incredible and results are amazing. Conclusion- Effect of Pippali Churn in Udarshool is very effective.